2021
DOI: 10.1177/03000605211013550
|View full text |Cite
|
Sign up to set email alerts
|

Ivermectin in combination with doxycycline for treating COVID-19 symptoms: a randomized trial

Abstract: Objective We evaluated whether ivermectin combined with doxycycline reduced the clinical recovery time in adults with COVID-19 infection. Methods This was a randomized, blinded, placebo-controlled trial in patients with mild-to-moderate COVID-19 symptoms randomly assigned to treatment (n = 200) and placebo (n = 200) groups. The primary outcome was duration from treatment to clinical recovery. Secondary outcomes were disease progression and persistent COVID-19 positivity by RT-PCR. Results Among 556 screened pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
61
3
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 25 publications
3
61
3
2
Order By: Relevance
“…Mahmud et al (15) found lower 14 th day RTPCR positivity rate in intervention group (7.6%) (received tablet ivermectin 12mg on day 1 and tablet doxycycline 100mg twice daily for 5 days) compared to the placebo group (20.0%) which was unlike our observations. However, due to the use of different intervention and day of RTPCR testing, results of Mahmud et al (15) and our study is not completely comparable. Moreover, it has been suggested that prolonged viral RNA shedding may continue for weeks after recovery leading to a false positive RT-PCR report even though the patient may not be infectious anymore (26).…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Mahmud et al (15) found lower 14 th day RTPCR positivity rate in intervention group (7.6%) (received tablet ivermectin 12mg on day 1 and tablet doxycycline 100mg twice daily for 5 days) compared to the placebo group (20.0%) which was unlike our observations. However, due to the use of different intervention and day of RTPCR testing, results of Mahmud et al (15) and our study is not completely comparable. Moreover, it has been suggested that prolonged viral RNA shedding may continue for weeks after recovery leading to a false positive RT-PCR report even though the patient may not be infectious anymore (26).…”
Section: Discussioncontrasting
confidence: 81%
“…Considering use of ivermectin in treatment of COVID-19 patients, several randomised controlled trials (RCTs) documented its beneficial role either as an additional monotherapy or in combination with doxycycline irrespective of severity of the disease (13)(14)(15). COVID-19 patients treated with ivermectin reported to have decreased duration of symptoms, days to COVID negativity (DTN), lower viral load, mortality rate and higher SPO2%, platelet count and improvement of other prognostic laboratory parameters (13)(14)(15)(16)(17). A metanalysis (18) and several prior observational studies (19)(20)(21) have also documented similar observations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, based on the current literature, a 10-day combination therapy of IVM, doxycycline and zinc will not only improve symptoms [6,7] but also accelerate recovery from COVID-19. We have chosen a safe IVM dosage approved for parasites of 36mg over 10 days, and this dose has been shown to be both effective and safe in COVID-19 treatments [38].…”
Section: Discussionmentioning
confidence: 98%
“…Current evidence regarding the efficacy of ivermectin for the treatment of COVID-19 patients is still unclear [21,22], and the WHO recommends its use only for clinical studies [23]. Therefore, the aim of this study is to evaluate the efficacy of ivermectin in preventing hospitalizations in patients with COVID-19 (IVERCOR-COVID19) [24].…”
Section: Introductionmentioning
confidence: 99%